ZIF-8/PI Nanofibrous Membranes With High-Temperature Resistance for Highly Efficient PM0.3 Air Filtration and Oil-Water Separation - Li, Yu; Wang, Dan; Xu, Guanchen; Qiao, Li; Li, Yong; Gong, Hongyu; Shi, Lei; Li, Dongwei; Gao, Meng; Liu, Guoran; Zhang, Jingjing; Wei, Wenhui; et al. (Frontiers in Chemistry, 2021)
Air and water pollution poses a serious threat to public health and the ecological environment worldwide. Particulate matter (PM) is the major air pollutant, and its primary sources are processes that require high temperatures, such as fossil fuel combustion and vehicle exhaust. PM0.3 can penetrate and seriously harm the bronchi of the lungs, but it is difficult to remove PM0.3 due to its small size. Therefore, PM0.3 air filters that are highly efficient and resistant to high temperatures must be developed. Polyimide (PI) is an excellent polymer with a high temperature resistance and a good mechanical property. Air filters made from PI nanofibers have a high PM removal efficiency and a low air flow resistance. Herein, zeolitic imidazolate framework-8 (ZIF-8) was used to modify PI nanofibers to fabricate air filters with a high specific surface area and filtration efficiency. Compared with traditional PI membranes, the ZIF-8/PI multifunction nanofiber membranes achieved super-high filtration efficiency for ultrafine particles (PM0.3, 100%), and the pressure drop was only 63 Pa. The filtration mechanism of performance improvement caused by the introduction of ZIF-8/PI nanofiber membrane is explored. Moreover, the ZIF-8/PI nanofiber membranes exhibited excellent thermal stability (300 oC) and efficient water–oil separation ability (99.85 %). The ZIF-8/PI nanofiber membranes can be applied in air purification equipment, filtration and detection, medical treatment environment purification and also could provide guidance in isensor and imedicine for human health, promoting the development of global health.